Evaluation of expression profiles of APOA4, CEACAM1, CD147, DJ-1/PARK7, Gamma-synuclein, S100A1, and Stathmin-1 in urothelial carcinomas using immunohistochemical assays - Sharif, Naveed; Shah, Walayat; Ali, Asif; Ali Khan, Taj; Nishan, Umar; Alobaid, Hussah M.; Safi, Sher Zaman; Rizv, Syed A. A.; Muhammad, Nawshad (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the diagnostic performance of APOA4, CEACAM1, CD147, DJ-1/PARK7, Gamma-synuclein, S100A1, and Stathmin-1 in urothelial carcinoma and establish optimal immunohistochemical cutoffs for their use as diagnostic markers.MethodThis cross-sectional study included 141 histologically confirmed urothelial carcinoma cases and controls. Immunohistochemical staining was optimized for each biomarker, and semiquantitative scoring was applied. Diagnostic validity was assessed using receiver operating characteristic (ROC) analysis, comparing sensitivity and specificity across several cutoffs and biomarker panels.ResultsAmong seven biomarkers, APOA4, DJ-1/PARK7, Gamma-synuclein, and Stathmin-1 demonstrated high diagnostic accuracy (≥80% sensitivity and specificity). Using an Allred score ≤2 as a cutoff, the sensitivity/specificity were as follows: APOA4, 96%/100%; DJ-1/PARK7, 97%/94%; Gamma-synuclein, 98%/84%; and Stathmin-1, 98%/90%. A combined panel of these four biomarkers achieved near-perfect diagnostic performance, reaching almost 100% sensitivity and specificity.ConclusionA biomarker panel comprising Stathmin-1, DJ-1/PARK7, Gamma-synuclein, and APOA4 reliably distinguished urothelial carcinoma from benign urothelium. These markers, when integrated with cytology, could enhance the diagnostic precision and reduce dependence on invasive cystoscopy. The proposed cutoffs (10%–20% positive cells or Allred score ≤2) offer clinically actionable threshold for histopathological practice.